2020
DOI: 10.37796/2211-8039.1017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the level of biomolecules isolated from date palm seeds (Phoenix dactylifera L) and in vitro Antioxidant property

Abstract: Date palm fruits and by-products such as seeds are a source of various elements with significant nutritional values like fibres, minerals, essential fatty acids, amino acids and phenolic compounds. The experimental part was carried out on date palm seeds from Bent Kbala cultivar, the chemical composition of the organic fraction was determined using the method of UV-visible spectrophotometer, thin layer chromatography (TLC) and high-performance liquid chromatography-diode array detection (HPLC-DAD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…With respect to state of the art works, it has been shown that the molecules potentially have antioxidant activities for an IC50 < 500 µg/mL [ 87 ]. With respect to the present sample showing an IC 50 < 100 µg/mL, in previous research performed by Bentrad and Gaceb-Terrak, [ 88 ], since the lowest IC 50 reveals the most significant antioxidant activity when compared to other standard antioxidants, the antioxidant activity is actually directly related to the extract concentrations [ 88 ].…”
Section: Resultsmentioning
confidence: 62%
“…With respect to state of the art works, it has been shown that the molecules potentially have antioxidant activities for an IC50 < 500 µg/mL [ 87 ]. With respect to the present sample showing an IC 50 < 100 µg/mL, in previous research performed by Bentrad and Gaceb-Terrak, [ 88 ], since the lowest IC 50 reveals the most significant antioxidant activity when compared to other standard antioxidants, the antioxidant activity is actually directly related to the extract concentrations [ 88 ].…”
Section: Resultsmentioning
confidence: 62%
“…Likewise, previous results reported a rich elemental composition of date seed powder attaining high amounts of Ca, K and Mg [ 30 ]. Furthermore, high levels of antioxidant compounds including phenolics, flavonoids, carotenoids and sterols were previously demonstrated in DPS [ 17 , 30 ]. Elicitation strategies usually rely on triggering the expression of genes involved in the plant stress response via the activation of specific receptors in the plasma membrane [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The costless seeds of date palm plants are a source of many components with high nutritional value such as oil, fibers, minerals, proteins, amino acids, fatty acids and phenolic compounds [ 16 ]. The date seeds exhibited high antioxidant activity when compared to standard antioxidants due to their phenolic compounds such as naringenin and rutin [ 17 ]. The rich contents make date palm seeds (DPS) a convenient organic application for eliciting plant secondary metabolism and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Bentrad and colleagues (2020) found an antioxidant property of date seeds extracted from the Bent Kbala cultivar using the DPPH method [ 36 ]. DSEs demonstrated the highest free radical inhibition rate (89.89 ± 0.02%) and antioxidant activity (IC 50 = 0.031 μg/mL) compared to other natural antioxidants.…”
Section: Biological Activities Of Date Seedsmentioning
confidence: 99%